2006
DOI: 10.4049/jimmunol.176.12.7686
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of IFN-λ in Murine Tumor Models

Abstract: IFN-λ 1, -λ 2 and -λ 3 have been discovered as the latest members of the class II cytokine family and shown to possess antiviral activity. Murine B16 melanoma and Colon26 cancer cells were transduced with mouse IFN-λ to determine whether IFN-λ possesses antitumor activity. Overexpression of IFN-λ induced cell surface MHC class I expression and Fas/CD95 Ag, induced significant caspase-3/7 activity, and increased p21Waf1/Cip1 and dephosphorylated Rb (Ser780) in B16 cells in vitro. IFN-λ expression in tumor cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
177
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(184 citation statements)
references
References 49 publications
(51 reference statements)
5
177
2
Order By: Relevance
“…We confirmed the broad expression pattern of the IFNAR system, and found that among the cell types examined, that pDCs were the only hemopoietic cell type that responded to IFN-. Others have reported that human monocytes, blood monocyte-derived DCs, and murine intrahepatic CD3 Ϫ DX5 ϩ NK cells respond to IFN-or express the receptor chains (28,29,47,49). Therefore, we conclude that only few cell types of the hemopoietic compartment are responsive to IFN-, although we cannot exclude that expression of the type III IFN receptor system may be induced by cell differentiation and activation in a broader spectrum of cells.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…We confirmed the broad expression pattern of the IFNAR system, and found that among the cell types examined, that pDCs were the only hemopoietic cell type that responded to IFN-. Others have reported that human monocytes, blood monocyte-derived DCs, and murine intrahepatic CD3 Ϫ DX5 ϩ NK cells respond to IFN-or express the receptor chains (28,29,47,49). Therefore, we conclude that only few cell types of the hemopoietic compartment are responsive to IFN-, although we cannot exclude that expression of the type III IFN receptor system may be induced by cell differentiation and activation in a broader spectrum of cells.…”
Section: Discussionmentioning
confidence: 52%
“…Others have reported that human blood monocytes gain responsiveness to IFNduring differentiation to DCs, and that these DCs induce proliferation of regulatory T cells (29) and modulation of the Th1/Th2 response (49). In a different study it was shown that intrahepatic CD3 Ϫ DX5 ϩ NK cells express the IFN-receptor chains and contribute to the antitumor activities of IFN- (28). Therefore, as with type I IFN, type III IFNs possess immunomodulatory activities, which suggests that the IFN-s can stimulate the antiviral host response through different mechanisms, and also that this class of cytokines has functions beyond antiviral defense, as already suggested (26 -28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the biological level, IFN-k1, IFN-k2, and IFN-k3 cytokines are more related to type I IFN, sharing the establishment of antiviral protection [97], antiproliferative [96], and antitumor [98][99][100] activities (reviewed in [101]). These cytokines activate the same JAK-STAT pathway, leading to the activation of STAT1/STAT2/IRF9 transcription factor complexes [4,5,96].…”
Section: Il-24mentioning
confidence: 99%
“…More than 300 genes regulated by IFNs are implicated in apoptosis (15)(16)(17)(18). Previous studies have demonstrated the antitumor potential of type III IFNs in mouse melanoma (19) and fibrosarcoma (20,21), human colorectal adenocarcinoma (22), glioblastoma (23), pancreatic neuroendocrine tumor (24) and colorectal carcinoma (25). There is also a report indicating that IFNλ induces apoptosis in non-small cell lung cancer (NSCLC) cells (26).…”
Section: Introductionmentioning
confidence: 96%